Treatment of chronic tonsillitis by Felix Anthony Erbrich, as described in GAZETA LEKARSKA, 1911 - Białoszycka, Monika Małgorzata; Białoszycka, Żanna; Simonova , Irina (Journal of Education, Health and Sport, 2026)
Introduction. At the beginning of the XX century, rare medical publications became part of the collection of the Scientific Library of Vinnytsia National Medical University named after M. I. Pyrohov. Among these holdings is the 1911 subscription of Gazeta Lekarska, a Warsaw-based medical journal, which published the works of Felix Anthony Erbrich (1874–1938), a prominent otolaryngologist and co-founder of the Polish Otolaryngological Society. Aim. The aim of this study was to highlight the scientific contributions of Dr. Felix Anthony Erbrich, focusing on his reports on tonsillar pathology and surgical treatment of chronic tonsillitis published in Gazeta Lekarska in 1911. Materials and Methods. The research is based on a historical case study and analysis of Erbrich’s clinical descriptions and surgical techniques applied at the Holy Spirit Hospital in Warsaw. Results and Discussion. Erbrich emphasized the role of chronic tonsillar infection as a source of systemic disease and illustrated his arguments with a detailed case report of prolonged febrile illness resolved by tonsillectomy. He criticized the limitations of partial tonsillotomy and advocated for complete enucleation of the tonsils. His modified technique, which used a silk ligature to retract and stabilize the tonsil, simplified and minimized intraoperative complications. Retrospectively, his insights anticipated modern understanding of tonsillar pathology and surgical standards in otolaryngology. Conclusions. F. A. Erbrich made an important contribution to early twentieth-century laryngology. Despite the challenging context of Russian-occupied Warsaw, his diagnostic reasoning, clinical practice, and surgical innovations corresponded to the contemporary requirements of specialized otolaryngological care.